(untitled) (European Science Methodical Journal, 2024)
Although the real world is three-dimensional, we mostly prefer to use two-dimensional tools in education. The combination of AR technology with educational content creates new types of automated applications and serves to increase the effectiveness and appeal of teaching and learning for students in real life. AR is a new tool that combines aspects of ubiquitous computing, material computing and social computing. This tool combines the physical and virtual worlds, offering unique capabilities with continuous and hidden control of the user’s perspective and interactivity. This article introduces AR technology (AR) and the capabilities of the software used in it.